ACUTE DISSECTING AORTIC ANEURYSM: CONSERVATIVE TREATMENT CASE - A. V. Yurchenko (Klinicist, 2014)
Clinical management of aortic wall dissection is defined by the type of stratification and development of associated complications. As an example, clinical case of conservative management of patients with acute aortic dissection is presented